Increased Extracellular Osteopontin Levels in Normal Human Breast Tissue at High Risk of Developing Cancer and Its Association With Inflammatory Biomarkers in situ - Lindahl, Gabriel; Rzepecka, Anna; Dabrosin, Charlotta (Frontiers in Oncology, 2019)
Mammographic breast density is a strong independent risk factor for breast cancer (BC), but the molecular mechanisms behind this risk is yet undetermined and prevention strategies for these women are lacking. The anti-estrogen tamoxifen may reduce the risk of BC but this treatment is associated with severe side effects. Thus, other means for BC prevention, such as diet interventions, need to be developed. Osteopontin (OPN) is a major mediator of inflammation which is key in carcinogenesis. OPN may be cleaved by proteases in the tissue and cleaved OPN may in turn induce an inflammatory cascade in the extracellular microenvironment. We aimed to determine if extracellular OPN was altered in BC and in normal breast tissue with different densities and if tamoxifen or a diet of flaxseed could modify OPN levels. The study comprised 103 women; 13 diagnosed with BC, 42 healthy postmenopausal women with different breast densities at their mammography screen, and 34 postmenopausal women who added 25 gram of ground flaxseed/day or were treated with tamoxifen 20 mg/day and were investigated before and after six weeks of exposure. Additionally, 10 premenopausal women who added flaxseed for one menstrual cycle and 4 who were investigated in two unexposed consecutive luteal phases of the menstrual cycle. Microdialysis was used to sample extracellular proteins in vivo in breast tissue and proteins were quantified using a multiplex proximity extension assay. We found that, similar to BC, extracellular in vivo OPN levels were significantly increased in dense breast tissue. Additionally, significant correlations were found between OPN and chemokine (C-X-C motif) ligand (CXCL)-1, -8, -9, -10 and -11, interleukin-6, vascular endothelial growth factor, matrix metalloproteinase (MMP)-1, -2, -3, 7, and -12 and urokinase-type plasminogen activator whereas no correlations were found with MMP-9, chemokine (C-C motif) ligand (CCL)-2 and -5. Estradiol did not affect OPN levels in breast tissue. None of the interventions altered OPN levels. The pro-tumorigenic protein OPN may indeed be a molecular target for BC prevention in women with increased breast density but other means than tamoxifen or flaxseed i.e. more potent anti-inflammatory approaches, need to be evaluated for this purpose.